Enhancing public service innovation through value co-creation: Capacity building and the 'innovative imagination'. Issue 5 (4th July 2022) - Hardyman, Wendy; Garner, Steve; Lewis, James J.; Callaghan, Robert; Williams, Emyr; Dalton, Angharad; Turner, Alice
IMPACT: Funders, policy-makers and public service managers should be aware that inputs can be designed into the innovation process in order to build capacity among staff engaged in innovation in public services. The article shows that upskilling, cohort creation and an enhanced innovative mindset can be generated through a structured programme, with the integration, application and use of such resources facilitating value co-creation processes. Barriers to and facilitators of innovation are also identified. These include senior management buy-in and allocation of time.